Effect of suspended particles with different grain sizes on the bioaccumulation of PAHs by zebrafish (Danio rerio). (March 2020) - Zhai, Yawei; Xia, Xinghui; Wang, Haotian; Lin, Hui
Abstract: The physicochemical characteristics are different for suspended particles (SPS) with different sizes in rivers. Here, we studied the effect of SPS (1 g L −1 ) with three different sizes (63–106 μm, 20–63 μm, and <20 μm) on the bioaccumulation of deuterated polycyclic aromatic hydrocarbons (phenanthrene-d10, anthracene-d10, fluoranthene-d10 and pyrene-d10) in zebrafish using passive dosing devices to maintain the freely dissolved concentrations of PAHs-d10 constant in water. The results showed that all the three grain size SPS could be ingested by zebrafish, and there was no significant difference in the amount of ingested SPS among the three grain sizes. The concentrations (lipid-normalized or not) of PAHs-d10 in zebrafish were promoted in the presence of the three different size SPS, and the PAH-d10 concentrations in zebrafish increased with decreasing particle size. Compared with the systems without SPS, the lipid-normalized concentrations of PAHs-d10 increased by 12%–72%, 34%–130%, and 60%–196%, respectively in zebrafish in systems with 63–106 μm, 20–63 μm, and <20 μm of SPS after exposure for 20 h. The stronger effect of SPS with smaller grain sizes was probably due to their lower organic carbon content, lower ratio of black carbon to organic carbon content, smaller particle size, and higher dissolved organic matter contents, which could promote the desorption of PAHs-d10 from ingested SPS and bioaccessibility of PAHs-d10 to zebrafish. This study suggests that in addition to SPS concentration, the suspended particle size should be considered in ecological risk assessment for hydrophobic organic compounds in aquatic environment. Highlights: SPS grain size did not significantly affect the amount of SPS ingested by zebrafish. The ingestion of SPS led to an increase in the body burden of PAHs-d10 in zebrafish. The body burden of PAHs-d10 in zebrafish increased with decreasing SPS grain size. SPS grain size affected the bioaccessibility of PAHs-d10 bound with SPS to zebrafish.